MAIN DIRECTIONS FOR IMPROVING THE PENSION SYSTEM IN UZBEKISTAN (Conferencea, 2022)
Social security is an objective process, the purpose of which is the ever-increasing, more complete and highquality satisfaction of the needs, first of all, of disabled citizens. And the higher the level of this satisfaction, the more civilized and socio-economically fair is the economic social system, which manifests itself in the maximum care of all categories of citizens and contributes to the activation of the human factor, the higher the level of political structure and humanistic social relations. The higher the level of social protection for all strata of society with priority allocation of socially vulnerable and poor strata, the greater the number of citizens covered by social security, the higher the level of social relations and the higher the standard of living of the population.